Anti –MBP autoantibody changes as a predictor of response to treatment in MS patients - Gholinejad, Khadijeh; Rahimipour, Ali; Sahraian, Mohammad Ali; Namaki, Saeed; Kazerouni, Faranak; Moghadasi, Abdorreza Naser; Rahimi, Forough; Boroumandnia, Nasrin (Archives of Advances in Biosciences, 2016)
Myelin basic protein (MBP) is one of the most important constituents of the CNS myelin sheaths. It is supposed that an autoimmune response directed against MBP is crucial in the demyelination process in patients with multiple sclerosis. Studies have proved that free anti-MBP level in CSF of MS patients is declined when the patient entered into clinical remission. Some researchers evaluate the changes in serum or CSF level of this antibody during immunomodulatory therapy; the results are different and the relation between the changes in this antibody and response to treatment is poorly investigated. The objective of this study was to assess the relation between the changes in serum level of anti-MBP and clinical remission in patients during treatment with fingolimod. 37 MS patients that were non responder to interferon and glatiramer acetate and were candidates to receive fingolimod were nominated for this study. In this study, the serum level of anti-MBP was evaluated before and after 3 and 6 months of therapy and clinical remission was assessed by changes in Expanded Disability Status Scale (EDSS) scores. The result of this study showed that MS patients, after treatment with interferon, have lower serum anti-MBP level than healthy control group and this difference is statistically significant (p =0.03). The present study demonstrated that the serum anti-MBP level in MS patient during 6 months of treatment with fingolimod significantly decreased (p<0.001). However, there was no significant difference in EDSS of MS patients during 6 months of treatment with fingolimod ( p < 0.001).